The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/bit.24894
|View full text |Cite
|
Sign up to set email alerts
|

Segregated flux balance analysis constrained by population structure/function data: The case of PHA production by mixed microbial cultures

Abstract: In this study we developed a segregated flux balance analysis (FBA) method to calculate metabolic flux distributions of the individual populations present in a mixed microbial culture (MMC). Population specific flux data constraints were derived from the raw data typically obtained by the fluorescence in situ hybridization (FISH) and microautoradiography (MAR)-FISH techniques. This method was applied to study the metabolic heterogeneity of a MMC that produces polyhydroxyalkanoates (PHA) from fermented sugar ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…Despite different uptake rates being obtained when each carbon source was fed individually and mixed with other VFAs, MAR-FISH showed the preference for each VFA by these genera. The selected culture had a highly flexible physiology allowing co-dominance between three main genera that could lead to improved models where the fraction of each PHA-producing population and their corresponding substrate preferences would be incorporated (Pardelha et al 2013). Queirós et al (2014) used hardwood sulfite spent liquor (HSSL), a by-product from the pulp industry, as substrate to acclimatize a MMC and attest its possible valorization.…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…Despite different uptake rates being obtained when each carbon source was fed individually and mixed with other VFAs, MAR-FISH showed the preference for each VFA by these genera. The selected culture had a highly flexible physiology allowing co-dominance between three main genera that could lead to improved models where the fraction of each PHA-producing population and their corresponding substrate preferences would be incorporated (Pardelha et al 2013). Queirós et al (2014) used hardwood sulfite spent liquor (HSSL), a by-product from the pulp industry, as substrate to acclimatize a MMC and attest its possible valorization.…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…The flux predictions given by the segregated model by were slightly better than those obtained by nonsegregated FBA, and coincided with metabolic flux analysis (MFA) estimated fluxes (Pardelha et al 2013). Even though this model does not predict population dynamics it can be a tool to describe the metabolic diversity among the distinct microorganisms in a mixed culture.…”
Section: Pha Synthesissupporting
confidence: 50%
“…The microbial community composition during the PHA production phase has been considered in the segregated FBA model method proposed by Pardelha et al (2013). The flux predictions given by the segregated model by were slightly better than those obtained by nonsegregated FBA, and coincided with metabolic flux analysis (MFA) estimated fluxes (Pardelha et al 2013).…”
Section: Pha Synthesismentioning
confidence: 76%
“…Moreover, high temperature may affect the enzyme activity of PHA synthetase. Pardelha et al (2013) found out that the increasing temperature would decrease the dissolved oxygen in the culture, and this phenomenon would lead to a decrease of PHB yield.…”
Section: Preliminary Optimization Of Pha Productionmentioning
confidence: 98%